(untitled) (PHILM. Rivista di filosofia e cinema, 2024)
The film N.Y., N.Y. by Francis Thompson is an example of an urban symphony, as it employs a system of prismatic and deforming lenses, mirrors, and kaleidoscopes to distort the appearance of the cityscape. This distortion is integrated into the frame through montage, creating a unique visual representation of the urban environment. By examining two key formal elements of the film – multiplication and kaleido-taumascopic distortion – we aim to explore how cinema and montage can evoke the distinctive experience of time in a metropolis and illustrate the reversal of the relations between time and movement as postulated by Gilles Deleuze with regard to the time-image.